A review on emission analysis in cement industries - Ali, M.B.; Saidur, Rahman; Hossain, M.S. (Elsevier, 2011)
The cement subsector consumes approximately 12-15 of the total industrial energy use. Therefore, this subsector releases CO 2 emissions to the atmosphere as a result of burning fossil fuels to produce energy needed for the cement manufacturing process. The cement industry contributes about 7 of the total worldwide CO 2 emissions. This study complied a comprehensive literature in terms of Thesis (MS and PhD), peer reviewed journals papers, conference proceedings, books, reports, websites for emission generation and mitigation technique. Emission released associated with the burning of fuels have been presented in this paper. Different sources of emissions in a cement industry has been identified and presented in this study. Different techniques to reduce CO 2 emissions from the cement manufacturing industries are reviewed and presented in this paper. The major techniques are: capture and storage CO 2 emissions, reducing clinker/cement ratio by replacing clinker with different of additives and using alternative fuels instead of fossil fuels. Apart from these techniques, various energy savings measures in cement industries expected to reduce indirect emissions released to the atmosphere. Based on review results it was found that sizeable amount of emission can be mitigated using different techniques and energy savings measures.